2007
DOI: 10.1111/j.1365-2354.2006.00741.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in lung cancer patients: impact of baseline clinical profile and respiratory status

Abstract: As cure is attainable in very few cases of lung cancer, the imperative issue is to make quality of life (QOL) as good as possible as part of the palliative care package. The aim of this paper was to evaluate the baseline QOL of lung cancer patients and observe its association with various clinical parameters and overall respiratory status. A total of 101 patients were administered the European Organization for Research and Treatment of Cancer core quality of life (EORTC QLQ-C30, version 3) questionnaire. Clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
2
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 45 publications
(57 reference statements)
1
21
2
6
Order By: Relevance
“…Patients with metastatic non-small cell lung cancer suffer from a poor prognosis, as seen from both studies presented here where the prognosis was poor, and previous studies have demonstrated that elderly patients suffer from a wide constellation of cancerrelated symptoms, including depression, guilt, debility, pain, and dyspnea. [10][11][12][13] Although the present study did not observe an association between social support and clinical outcomes, there nonetheless remains a strong need for maximizing social support to help with some of the cancer-related challenges these patients face.…”
Section: Dovepresscontrasting
confidence: 73%
See 1 more Smart Citation
“…Patients with metastatic non-small cell lung cancer suffer from a poor prognosis, as seen from both studies presented here where the prognosis was poor, and previous studies have demonstrated that elderly patients suffer from a wide constellation of cancerrelated symptoms, including depression, guilt, debility, pain, and dyspnea. [10][11][12][13] Although the present study did not observe an association between social support and clinical outcomes, there nonetheless remains a strong need for maximizing social support to help with some of the cancer-related challenges these patients face.…”
Section: Dovepresscontrasting
confidence: 73%
“…9 At the same time, however, lung cancer patients specifically have greater needs for social support because of diminished mobility, concomitant morbidity, and an accelerated decline in overall health status. [10][11][12][13] Thus, the literature on social support raises questions relevant to geriatric lung cancer patients and women in particular.…”
Section: Dovepressmentioning
confidence: 99%
“…O perfil epidemiológico dos pacientes com câncer de pulmão em nosso estudo coincide com trabalhos prévios, com predominância das seguintes características: sexo masculino, faixa etária média acima de 60 anos, fumantes [15][16][17] , tipo histológico adenocarcinoma, e estadiamento IIIB e IV nos casos de CPNPC [16][17][18][19] epidermoide, mas ambos estão relacionados ao tabagismo 20,21 . Os sintomas pré-tratamento mais frequentemente relatados pelos nossos pacientes foram os respiratórios.…”
Section: Discussionunclassified
“…Estudo prévio demonstrou significativa correlação entre CVF, VEF 1 , PFE e escalas funcionais da QV, principalmente função física, em pacientes com câncer de pulmão. A capacidade de exercício também apresentou correlação positiva com as escalas funcionais 19 . Outro estudo identificou que VEF 1 < 70% do previsto, o número de comorbidades e o número total de sintomas respiratórios, sendo a dispneia o principal, eram alguns preditores de redução da funcionalidade física, assim como na limitação física, saúde geral e função social 30 .…”
Section: Discussionunclassified
“…Although chemotherapy and radiotherapy are widely used, the role of these types of treatment in increasing survival and principally in improving quality of life is still subjective. (5,6) In patients with advanced lung cancer, chemotherapy has been shown to have advantages over palliative treatment. (7) However, these patients experience symptoms and side effects, such as nausea, vomiting, infection, loss of appetite, and fatigue, which have been associated with reduced exercise capacity, inactivity, and impaired quality of life.…”
Section: Introductionmentioning
confidence: 99%